2014
DOI: 10.1177/0954409714530911
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the mechanics of rail seat deterioration and methods to improve the abrasion resistance of concrete sleeper rail seats

Abstract: A sustained increase in gross rail loads and cumulative freight tonnages on heavy haul railways, as well as increased interest in high-and higher-speed passenger rail development, is placing an increasing demand on railway infrastructure and its components. Rail seat deterioration (RSD) refers to the degradation of the material at the contact interface between the sleeper's rail seat and the pad that protects the bearing area of the sleeper. RSD continues to be identified as one of the primary factors limiting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…In 2010, a laboratory test apparatus and procedure were devised by Zeman to investigate the influence of hydraulic pressure cracking, hydro-abrasive erosion, and cavitation erosion, and several suggestions to mitigating RSA were given [9,10]. Borg et al performed large-scale abrasion tests in 2014 [15], based on the results of the experiments, they concluded that the frictional characteristics between a rail pad and rail seat had an impact on the transfer of forces and relative movement and could influence RSA. Kaewunruen et al [16] presented a nonlinear finite element model to evaluate influences of surface abrasions on dynamic behaviours of railway concrete sleepers.…”
Section: Introductionmentioning
confidence: 99%
“…In 2010, a laboratory test apparatus and procedure were devised by Zeman to investigate the influence of hydraulic pressure cracking, hydro-abrasive erosion, and cavitation erosion, and several suggestions to mitigating RSA were given [9,10]. Borg et al performed large-scale abrasion tests in 2014 [15], based on the results of the experiments, they concluded that the frictional characteristics between a rail pad and rail seat had an impact on the transfer of forces and relative movement and could influence RSA. Kaewunruen et al [16] presented a nonlinear finite element model to evaluate influences of surface abrasions on dynamic behaviours of railway concrete sleepers.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, failure modes such as abrasion and high hydraulic pressures, which can lead to rail seat deterioration, are unable to be detected through visual inspection. The detection of rail seat deterioration would require the lifting of rail and removal of rail pad (Kernes et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It is desirable that the sleeper is free of cracks under dynamic loading, because if cracks occur, there is a great increase in stresses in the prestressing reinforcement and an increase of up to 50% in the transfer length [14][15][16]. Therefore, designing a prestressed sleeper is a good solution to avoid problems with simple concrete [1,15,17,18].Thus, this paper aims to evaluate the mechanical behavior of prestressed concrete sleepers, in accordance with the Brazilian and American standards and the common pathologies they are submitted to over their design life. A comparison is made between the results obtained numerically by the software ABAQUS and the experimental curves obtained through the tests, as recommended by ABNT NBR 11709 [19] and AREMA [20].…”
mentioning
confidence: 99%
“…A comparison is made between the results obtained numerically by the software ABAQUS and the experimental curves obtained through the tests, as recommended by ABNT NBR 11709 [19] and AREMA [20]. Eighteen experimental tests in sleepers were carried out, in order to validate the nonlinear numerical model, using ABAQUS [18]. In addition, using the validated numerical model, the influence of the combined effect of rail seat abrasion and corrosion in the load-carrying capacity of the sleepers was evaluated [4,10,[21][22][23].…”
mentioning
confidence: 99%
See 1 more Smart Citation